Regresi Data Panel dalam Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran Terbuka di Provinsi Daerah Istimewa Yogyakarta Tahun 2017-2021 - Pamuji, Agung; Setiawan, Ezra Putranda; Munir, Amir Mishbahul (Universitas Sebelas Maret, 2023)
Open unemployment is one of the most important problems in a country's economy. High unemployment rates can cause serious economic impacts, such as reduced productivity, poverty, and social instability. This problem is one that currently being faced by Indonesia, including in the Province of Special Region of Yogyakarta. This study aims to analyze the factors that influence the open unemployment rate in the Special Region of Yogyakarta Province in the 2017-2021 period. The factors tested include the Human Development Index (HDI), Regional Gross Domestic Product (Regional GDP), and District/City Minimum Wage. This study uses the panel data regression method using annual data from each district/city in the Special Region of Yogyakarta Province during the 2017-2021 period. The results showed that the Human Development Index (HDI) and District/City Minimum Wage variables positively and significantly affected the open unemployment rate in Special Region of Yogyakarta Province during the study period. Meanwhile, the GRDP variable has an insignificant effect on the open unemployment rate in the Special Region of Yogyakarta Province.Keywords: Data Panel; TPT; IPM; UMK; PDRB